A comparative study of prothrombin complex concentrates and freshfrozen plasma for warfarin reversal under static and flow conditions - Ogawa, Satoru; Szlam, Fania; Ohnishi, Tomoko; Molinaro, Ross J.; Hosokawa, Kazuya; Tanaka, Kenichi A. (Thrombosis and Haemostasis, 2011)
Prothrombin complex concentrates (PCCs) and fresh-frozen plasma (FFP) have been clinically used for acute warfarin reversal. The recovery of prothrombin time (PT) or international normalised ratio (INR) is often reported as an endpoint, but haemostatic efficacies of PCCs and FFP may not be fully reflected in static clotting test in platelet-poor plasma. Using various in vitro assays, we compared the effects of two PCC preparations (3-factor PCC; Bebulin and 4-factor PCC; Beriplex) and FFP on warfarin reversal under static and flow conditions. First, we added an aliquot of either PCC (0.3 or 0.72 U/ml) or 20% FFP (v/v) to commercial warfarin plasma (INR 3.2, or 10.3), and then measured PT, factor II, factor VII, and thrombin generation. Subsequently, we collected whole blood samples from six consented warfarin-treated patients with mean INR 3.0 ± 0.5 (range 2.5–3.7), and compared clot formation under flow conditions at 280 s-1 before and after addition of either PCC preparation (0.3 and 0.6 U/ml) or 20% of FFP (v/v). PT/INR were restored by either PCC in plasma with INR 3.0, but they were more effectively corrected by 4-factor PCC than 3-factor PCC in plasma with INR 10.3. Effects of FFP were similar to 0.3U/ml of PCCs in terms of PT, but FFP was less efficacious than PCCs in recovering thrombin generation or factor II levels. In flow experiments, the onset of thrombus formation was shortened by either PCC, but not by FFP, contrary to shortened PT values. For warfarin reversal 20% volume replacement with FFP is inferior to PCCs.
Keywords: Thrombosis; factor concentrates; vitamin K-dependent factors; blood products